HIGH SCHOOL FEMALE STUDENTS’ SATISFACTION DEGREE AFTER PRACTICING SPECIFIC AQUAGYM PROGRAMS AS AN EXTRACURRICULAR ACTIVITY - GEORGESCU (BĂRȚĂGUI-GEORGESCU), Carmen-Mariana; ORȚĂNESCU, Dorina; IORDĂCHESCU (ELENA), Marina; JURCA, Maria Oana (Studia Universitatis Babeş-Bolyai Educatio Artis Gymnasticae, 2022)
Introduction. The aquatic environment offers numerous exercise opportunities with a focus on achieving sports performance, as well as a number of beneficial effects compared to the terrestrial environment. The biological adaptation to aquagym-specific exercises, supported by the physical properties of the aquatic environment, is the response of the body to physical stimuli leading to ameliorative changes in body functions. The novelty of the activity and the relative ease of this form of physical exercise stimulated and motivated the female participants in an aquagym program carried out in the 1st semester of the school year 2021-2022. Objective. Our statement is supported by the results obtained from carrying out a satisfaction survey which aimed to highlight the impact of aquatic recreational activities, namely aquagym, and the effectiveness of the means selected in the operational programs on motor and functional capacity. Materials and Methods. The study included 37 high school female students, aged 16-17, from “Carol I” National College in Craiova. In order to optimize the students’ motor skills, an aquagym-specific program of exercises was developed and carried out along 12 sessions of 50 minutes each. At the end of the program, an opinion questionnaire was administered addressing high school female students’ degree of satisfaction with the content of aquagym sessions. Results. The application of the questionnaire-based satisfaction survey highlighted the advantages of practicing aquagym ranging from bio-motor benefits, such as the increase in flexibility, balance and muscular strength, to aspects outlining the improvement in some components of quality of life. The result of this survey confirms that the aquagym program was appreciated by the students who became aware of the positive effects obtained. Conclusions. Our students’ participation in aquagym-specific programs revealed the need to improve the educational offer of the school subject Physical Education and to harmonize the contents of the classes with students’ options. The analysis of the survey findings shows that the students rated the recreational content higher than the effects on motor skills and, surprisingly, a very small percentage of the students appreciated the effects on body shaping. Received 2022 April 27; Revised 2022 July 20; Accepted 2022 July 21; Available online 2022 June 30; Available print 2022 August 30. REZUMAT. Gradul de satisfacție al elevelor de liceu după practicarea programelor specifice de aquagym ca activitate extracurriculară. Introducere. Mediul acvatic oferă numeroase oportunități de exerciții fizice, cu accent pe obținerea de performanțe sportive, precum și o serie de efecte benefice în comparație cu cele oferite de mediul terestru. Adaptarea biologică la exercițiile specifice aquagym-ului, susținută de proprietățile fizice ale mediului acvatic, este răspunsul organismului la stimuli fizici care provoacă modificări ameliorative ale funcțiilor corpului. Noutatea activității și relativa facilitate a acestei forme de practicare a exercițiului fizic a stimulat și motivat participantele la un program de aqugym, desfășurat în anul școlar 2021-2022, semestrul I. Obiectiv. Afirmația noastră este susținută de rezultatele obținute în urma aplicării unui chestionar de satisfacție care și-a propus să evidențieze impactul activității ludico-recreative acvatice, respectiv a aquagym-ului și eficiența mijloacelor selecționate în cadrul programelor operaționale asupra capacității motrice și funcționale. Materiale și metode. Studiul a inclus 37 de eleve de liceu cu vârsta cuprinsă între 16-17 ani de la Colegiul Național „Carol I” Craiova. Pentru optimizarea capacității motrice a elevelor s-a alcătuit un program de exerciții specifice aquagym-ului, desfășurat timp de 12 ședințe, cu o durată de 50 de minute. La sfârșitul programului a fost aplicat un chestionar de opinie vizând gradul de satisfacție al elevelor de liceu cu privire la conținutul ședințelor de aquagym. Rezultate. Aplicarea chestionarului de satisfacție a evidențiat avantajele practicării aquagym-ului pornind de la beneficiile bio-motrice, cum ar fi creșterea flexibilității, echilibrului și forței musculare, către aspecte ce conturează îmbunătățirea unor componente ale calității vieții. Rezultatul prezentei anchete confirmă faptul că programul de aquagym a fost apreciat de eleve, care, au conștientizat efectele pozitive obținute. Concluzii. Participarea la programele specifice aquagym-ului a evidențiat nevoia de îmbunătățire a ofertei educaționale la disciplina educație fizică și a racordării conținuturilor lecțiilor la opțiunile elevilor. Din analiza rezultatelor chestionarului se remarcă faptul că elevele apreciază mai mult conținutul recreativ, mai puțin efectele asupra capacității motrice și în mod surprinzător, un procent foarte mic au apreciat efectele asupra modelării corporale. Cuvinte cheie: program aquagym, capacitate motrică, sisteme de acționare, satisfactie, elevele de liceu